5(3m-2)-9(5-2m)=4m+2(5m+1

Simple and best practice solution for 5(3m-2)-9(5-2m)=4m+2(5m+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(3m-2)-9(5-2m)=4m+2(5m+1 equation:



5(3m-2)-9(5-2m)=4m+2(5m+1
We move all terms to the left:
5(3m-2)-9(5-2m)-(4m+2(5m+1)=0
We add all the numbers together, and all the variables
5(3m-2)-9(-2m+5)-(4m+2(5m+1)=0
We multiply parentheses
15m+18m-(4m+2(5m+1)-10-45=0
We add all the numbers together, and all the variables
33m-(4m+2(5m+1)-10-45=0

You can always share this solution

See similar equations:

| 3x+4=5-9 | | 9/x=98/7 | | 3x+17=32;3 | | 5x+3=15x+7 | | 261=152-v | | 5x+3+15x+7=180 | | 4x+5=17;3 | | 8/x^2-1-4/x-1=2/x+1 | | 23=3/1b–2+3/4b | | (4x-25)(2x-1)=180 | | 8y+–11y+8=17 | | -13+p=-10 | | 1.5x-(6)=7.5 | | 7x+4-2x=10x+16 | | 2x?3+4x=29 | | -x-20=6x+1 | | -4x-(18)=22 | | a+7-3(2a+5)=-2(a-15)-5 | | X+19=2x-20;-1 | | x/5-3x+7/10=1 | | 3u+64=11u | | f(2)=1.5(2)+1 | | 8(x-3)=8x+40 | | 2x-14+2x=4(4x-5)+2 | | 3=1,5b | | | | | | 64=48/x | | 56-8x=32 | | 8x-34=5×+2 | | 5t²-40t-9=0 | | 4/28=7/x | | 6x+87=14x+47 |

Equations solver categories